The Understanding Of Ruling And Management Of Luqatah (lost Property) Among USIM Students - Muhammad Aunurrochim Mas'ad Saleh; Luqman Sharif@Hamzah (USIM PRESS, 2024)
Vol. 9 No. 2 (2021): MJSL - Volume 9, No. 2, 2021